2022
DOI: 10.1039/d1an02347k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electrochemical detection of ozone and free chlorine with a boron-doped diamond electrode

Abstract: O3 and free chlorine play significant roles in disinfection and organic degradation. There are numerous reports about their mixed-use, yet detection of the residual concentrations is not easily accomplished, whilst...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The authors previously reported free chlorine detection at BDD anode (equation 4) [66] . Also, cathodic reduction of HClO and hypochlorite ions (ClO − ) at BDD cathode were reported, which are represented by equation [67,68] Cl2+2normale2Cl- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm Cl}{_{2}}+{\rm 2e}\rightarrow {\rm 2Cl}{^{- }}\hfill\cr}}$ HClO+eHClO- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm HClO}+{\rm e}\rightarrow {\rm HClO}{^{- }}\hfill\cr}}$ 2HClO-Cl-+ClO-+H2O $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm 2HClO}{^{- }}\rightarrow {\rm Cl}{^{- }}+{\rm ClO}{^{- }}+{\rm H}{_{2}}{\rm O}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors previously reported free chlorine detection at BDD anode (equation 4) [66] . Also, cathodic reduction of HClO and hypochlorite ions (ClO − ) at BDD cathode were reported, which are represented by equation [67,68] Cl2+2normale2Cl- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm Cl}{_{2}}+{\rm 2e}\rightarrow {\rm 2Cl}{^{- }}\hfill\cr}}$ HClO+eHClO- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm HClO}+{\rm e}\rightarrow {\rm HClO}{^{- }}\hfill\cr}}$ 2HClO-Cl-+ClO-+H2O $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm 2HClO}{^{- }}\rightarrow {\rm Cl}{^{- }}+{\rm ClO}{^{- }}+{\rm H}{_{2}}{\rm O}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…[66] Also, cathodic reduction of HClO and hypochlorite ions (ClO À ) at BDD cathode were reported, which are represented by equation 5. [67,68] Cl 2 þ 2e ! 2Cl À (4)…”
Section: Attempt To Suppress Anodic Chloride Evolution Reaction (Cer)mentioning
confidence: 99%
“…Typical BDD films were grown on a silicon (100) substrate for 6 h with a microwave plasma chemical vapor deposition method, as reported previously . Methane and trimethyl borane was used as the carbon and boron sources, respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Typical BDD films were grown on a silicon (100) substrate for 6 h with a microwave plasma chemical vapor deposition method, as reported previously. 25 Methane and trimethyl borane was used as the carbon and boron sources, respectively. The boron concentration in the BDD films was set to 0.1 and 1% by adjusting the ratio of boron-to-carbon in the feeding gases.…”
Section: ■ Introductionmentioning
confidence: 99%